OPTIMALISASI PEMANFAATAN PERPUSTAKAAN SEKOLAH DALAM MENINGKATKAN MINAT BACA SISWA SEKOLAH DASAR - Nur Aeni, Yunita; Nurpratiwiningsih , Laelia; Tri Setiyoko, Didik (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
The promotion of reading interest is one of the key roles of the library as a source and provider of information. This study aims to formulate concrete steps to enhance students’ reading interest through the optimal utilization of elementary school libraries. The research method used is qualitative with a literature study approach, involving the analysis of various scholarly sources related to literacy, library management, and strategies to increase reading interest at the elementary level. The findings of the study indicate that optimization can be achieved through three main steps: (1) Library revitalization, which includes rearranging the space, providing a diverse and age-appropriate reading collection, and utilizing digital technology; (2) Implementation of literacy programs, such as reading corners, book review competitions, and sustainable group reading activities; and (3) Library staff training, to enable them to become active literacy facilitators who are responsive to students' needs. These three strategies complement each other and can be continuously developed by schools in an effort to establish a strong literacy culture from an early age.